Prediksi Kesetimbangan Uap-Cair Sistem Biner 3-Pentanol + Asam Propionat Sebagai Basis Pada Proses Desain Pemurnian Biofuel - Bekti, Andi Setyo; Paramitha, Pradnya; Altway, Saidah; Wibowo, Agung Ari (Prosiding Seminar Nasional Teknik Kimia "Kejuangan", 2023)
The depletion of fossil fuels has led to a turn toward renewable and cleaner diesel fuel. In recent years, research has focused on the development of green energy to replace fossil fuels. 3-Pentanol is the preferred alternative fuel because it has better fuel properties compared to other biofuels. 3-Pentanol, as a propionic acid derivative chemical platform, can be produced from renewable biomass through the lactic acid pathway. Therefore, to obtain 3-Pentanol with high purity, a purification process such as distillation is required. Vapor-liquid equilibrium data and the thermodynamic model parameters are needed as basis for designing a distillation column and optimizing the separation process. The aim of this study is to predict the vapor-liquid equilibria (VLE) of the binary systems of 3-Pentanol + propionic acid at 100 kPa, 200 kPa, and 300 kPa using the UNIFAC model in combination with the Hayden-O’Connell model. The prediction results showed no azeotropes found for the studied systems. This study can also open a scope for the thermodynamic studies of biofuel separation process.